2021
DOI: 10.1007/s10008-021-04999-7
|View full text |Cite
|
Sign up to set email alerts
|

Indium-doped ZnOas efficient photosensitive material for sunlight driven hydrogen generation and DSSC applications: integrated experimental and computational approach

Abstract: Electricity generation using simple and cheap dye sensitized solar cells and photocatalytic water splitting to produce future fuel, hydrogen, directly under natural sunlight fascinated the researchers world-wide. Herein, synthesis of indium doped wurtzite ZnO nanostructures with varying molar percentage of indium from 0.25 to 3.0% with concomitant characterization indicating wurtzite structure is reported. The shift of (002) reflection plane to higher 2θ degree with increase in indium doping thus is a clear ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Many theoretical research on indium in recent years have demonstrated that indium clusters have many great qualities in the areas of methane dehydrogenation, enhancing the stability of clusters like InnN 2 , and enhancing the photoactivity of TiO 2 [16][17][18]. Indium element also has a good performance in photocatalytic reaction, studies have shown that ZnInxSy, ZnO, and other clusters doping with appropriate amount of In can improve the photocatalytic hydrogen evolution activity [19][20][21]. To expand the research on hydrogen production from cluster dissociation of water, in view of the excellent properties of In clusters in many aspects, this research will start with In clusters to study the hydrogen evolution principle of the reaction between In clusters and H2O, and explore its performance in dissociating water to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical research on indium in recent years have demonstrated that indium clusters have many great qualities in the areas of methane dehydrogenation, enhancing the stability of clusters like InnN 2 , and enhancing the photoactivity of TiO 2 [16][17][18]. Indium element also has a good performance in photocatalytic reaction, studies have shown that ZnInxSy, ZnO, and other clusters doping with appropriate amount of In can improve the photocatalytic hydrogen evolution activity [19][20][21]. To expand the research on hydrogen production from cluster dissociation of water, in view of the excellent properties of In clusters in many aspects, this research will start with In clusters to study the hydrogen evolution principle of the reaction between In clusters and H2O, and explore its performance in dissociating water to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%